Subjective evaluation of the functional well-being of an athlete with a disability: key features, dependability, and external validity - Zakharova N.L. ,; Kotovskaya S.V. ,; Belenkova L.Yu. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creation and validation of a questionnaire-based approach to assess the performance of athletes with disabilities, focusing on the functionality of their body systems in relation to the demands of their sport. Methods and structure of the study. The framework for the creation of the methodology was based on the theoretical framework of functional comfort. The theoretical framework is a subsystem level of functional comfort, consisting of five subsystems that differ in their functional purpose and unique characteristics: sensory, cognitive, volitional, adaptive, and motor. The research methods used included testing, expert evaluation by coaches, analysis of training process data, assessment of the progress in developing sports skills, and examination of performance at competitions. The retest reliability was assessed in two stages, with a six-month interval between them. Results and conclusions. Based on the majority of scales, the retest reliability is strong and meets the psychometric standards. However, the cognitive subsystem scale stands out with inconsistent results. The internal consistency of the sensory and motor subsystems scale is average, suggesting that subjective functional comfort is influenced by external factors. The correlation analysis results indicate a satisfactory level of empirical validity. This method can be employed for scientific research and as a diagnostic tool for athletes with disabilities.